Effectiveness of Extension as a Means of Improving Knowledge About Malaria in Olaroa Village Kwamki Narama District, Mimika Regency in 2024 - Kose, Rahima; Riza Yuliawati; Arif Wijayanto (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2025)
Southeast Asia, especially Indonesia, is the second highest country in malaria cases. Malaria cases in Mimika Papua are still relatively high, namely from early January 2023 to the end of April 2023 in Mimika there were 31,383 cases (Ministry of Health of the Republic of Indonesia, 2023). This research is a type of quantitative research using Pre- Experimental research with a pretest-posttest design with a sample size of 50 respondents. This sampling was carried out using Non-Probability Sampling or (Non Random Sampling) with the sampling technique used in this study is accidental sampling. The results of the study were obtained from 50 respondents. There is an effect of health education on the level of knowledge about malaria in Olaroa Village, Kwamki Narama District, Mimika Regency in 2024. Before being given education or pre-test, respondents who had a high level of knowledge were 13 people or 26%, respondents who had a moderate level of knowledge were 24 people or 48%, and respondents who had a low level of knowledge were 13 people or 26%. After being given education or post-test, respondents who had a high level of knowledge were 38 people or 76%, respondents who had a moderate level of knowledge were 9 people or 18%, and respondents who had a low level of knowledge were 3 people or 6%.